Synthesis and Diuretic Activity of Substituted 1,3,4-Thiadiazoles - Asrat Ergena; Yerra Rajeshwar; Gebremedhin Solomon (Scientifica)
1,3,4-Thiadiazole nuclease, a 5-membered heterocyclic ring system containing two nitrogen and one sulfur atoms in addition to carbon atoms, is compound that showed promising results in the process of searching new diuretic agents. In this study, seven 5- and 2-thioate derivatives of 1, 3, 4-thiadiazoles were synthesized by substitution reaction using acetone as solvent and K2CO3 as a base. The compounds ware then characterized by using IR and NMR spectroscopy. The diuretic activity of the compounds was evaluated on Swiss albino mice by measuring urine volume, urinary pH, and urinary Na+, K+, and Cl−. The result showed increase in urinary excretion of both water and electrolytes. 5-Methyl-substituted derivatives of 1, 3, 4-thiadiazoles showed significant increase in excretion of both water and electrolytes when they are compared to both negative control and 5-amino-substituted derivatives. The highest diuretic activity (0.82) was recorded for para-nitro-substituted benzene ring at 2-thioate group of 5-methyl-1, 3, 4-thiadiazole, while the least (0.56) was recorded for propanethioate group at 2nd position and amine group at 5th position of 1, 3, 4-thiadiazole. The finding of the present study showed that all the compounds have diuretic activity and 5-methyl derivatives of 1, 3, 4-thiadiazoles exhibited significant diuretic activity.